Delusional infestation: an interface with psychiatry. (September 2021) - Waykar, Vijayendra; Wourms, Katherine; Tang, Michael; Joseph, Verghese
SUMMARY: Delusional infestation (delusional parasitosis) is a relatively rare condition but it has been of interest to a wide range of professionals, including entomologists, zoologists and dermatologists, as patients predominantly seek help from specialties other than psychiatrists. The illness requires a multidisciplinary approach and a strong bond of trust between the treating clinician and the patient to ensure the best possible outcome. This article discusses how clinicians in all specialties should approach patients presenting with the disorder and outlines differential diagnosis and associated laboratory tests. It considers the evidence base for treatment and the success of psychodermatology clinics that provide a 'neutral setting' for consultation to address the problem of patients' non-engagement. Such clinics are few, and there is a need to develop disease-specific pathways in primary care and hospital settings to improve prognosis.